Free, bioavailable 25-hydroxyvitamin D levels and their association with diabetic ketoacidosis in children with type 1 diabetes at diagnosis - Choe, Yunsoo; Lee, Yun Jeong; Kim, Jae Hyun; Lee, Kyunghoon; Shin, Choong Ho; Lee, Young Ah; Song, Junghan (Frontiers in Endocrinology, 2022)
Background: Considering the roles of 25-hydroxyvitamin D (25OHD) in glucose homeostasis and immune modulation, vitamin D deficiency may be related to the development of type 1 diabetes (T1DM) and diabetic ketoacidosis (DKA). We evaluated the total, free, bioavailable 25OHD levels and vitamin D binding protein (VDBP) levels and genotypes between T1DM patients and controls. Methods: This retrospective, cross-sectional study included 84 children with T1DM (38 boys and 46 girls, 8.0 ± 3.6 years) and 1:1 age- and sex-matched healthy controls. A multiplex liquid chromatography-tandem mass spectrometry-based assay was used to simultaneously measure vitamin D metabolites. Results: Patients with T1DM had lower levels of total 25OHD (16.3 ± 5.1 vs. 19.9 ± 6.5 ng/mL, P < 0.001) and VDBP (146.0 ± 27.8 vs. 224.9 ± 36.1 µg/mL, P = 0.001), but higher free 25OHD (8.0 ± 2.5 vs. 6.5 ± 2.3 pg/mL, P < 0.001) than controls. Patients who presented with DKA had lower levels of 25OHD in the total (15.0 ± 4.6 vs. 17.6 ± 5.2 ng/mL, P = 0.020), free (7.5 ± 2.6 vs. 8.4 ± 2.4 pg/mL, P = 0.059), and bioavailable (2.3 ± 0.9 vs. 2.8 ± 0.8 ng/mL, P = 0.014) forms than those without DKA at the T1DM diagnosis. The lower the total, free, and bioavailable 25OHD levels at diagnosis, the lower the pH and HCO3-. The proportions of the VDBP genotypes did not differ between the patients and controls. Conclusion: Patients with T1DM had higher levels of free 25OHD than healthy children, despite lower levels of total 25OHD. However, patients with DKA exhibited lower levels of bioavailable 25OHD than those without DKA at the T1DM diagnosis. The lower the concentrations of free and bioavailable 25OHD, the more severe the acidosis at the initial T1DM presentation.